2020
DOI: 10.3390/antiox9020127
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pectic Polysaccharide of Jujube Pomace: Structural Analysis and Intracellular Antioxidant Activities

Abstract: After extraction from jujube pomace and purification by two columns (DEAE-Sepharose Fast Flow and Sepharcyl S-300), the structure of SAZMP4 was investigated by HPGPC, GC, FI-IR, GC-MS, NMR, SEM, and AFM. Analysis determined that SAZMP4 (Mw = 28.94 kDa) was a pectic polysaccharide mainly containing 1,4-linked GalA (93.48%) with side chains of 1,2,4-linked Rha and 1,3,5-linked Ara and terminals of 1-linked Rha and 1-linked Ara, which might be the homogalacturonan (HG) type with side chains of the RG-I type, corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The bulk structure of AMP is more irregular compared to that of FMP. This suggests that the inter- and intramolecular aggregation caused by hydroxyl group interactions on the polysaccharide chains may have occurred as a disordered spontaneous self-assembly process during the storage of the raw material ( Lin et al, 2020 ). These results are consistent with the results of Section 3.2 (Molecular weight increase after raw material storage).…”
Section: Resultsmentioning
confidence: 99%
“…The bulk structure of AMP is more irregular compared to that of FMP. This suggests that the inter- and intramolecular aggregation caused by hydroxyl group interactions on the polysaccharide chains may have occurred as a disordered spontaneous self-assembly process during the storage of the raw material ( Lin et al, 2020 ). These results are consistent with the results of Section 3.2 (Molecular weight increase after raw material storage).…”
Section: Resultsmentioning
confidence: 99%
“…As for the FT-IR spectra of NPP (Fig. S2), the distinct peaks at 3419 and 2934 cm −1 belong to the stretching vibration of O–H and C–H bonds, respectively [ 34 ]. The peaks at 1728 and 1608 cm −1 are present due to the stretching vibrations of C=O bonds in ester and carboxyl, respectively [ 29 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The peaks located between 1200 and 1000 cm −1 correspond to the bending vibration of C–O–C glycosidic bonds in polysaccharide [ 37 , 38 ]. Note that the weak absorption peaks in the low frequency region of 900–800 cm −1 are probably related to α-glycosidic bonds, which implies the existence of α -glycosidic bonds in NPP [ 34 ]. These results demonstrate that the NPP certainly is abundant in oxygen-containing groups, which could afford a powerful adsorption toward Li 2 S n /Li 2 Se n and thus retard the shuttle effect.…”
Section: Resultsmentioning
confidence: 99%
“…HPLC analysis indicated that JCS-1 and JCS-2 were composed mainly of galacturonic acid (GalA) (Table 1). A recent study found that SAZMP4 (a novel antioxidant pectin isolated from jujube) was composed mainly of rhamnose, arabinose, xylose, mannose, and GalA through 1,4linked GalA (93.48%) (Lin et al, 2020).…”
Section: Polysaccharidesmentioning
confidence: 99%